ANALISIS YURIDIS ASAS PACTA TERTIIS NEC NOCENT NEC PROSUNT DALAM SUKSESI TIMOR TIMUR DARI WILAYAH INDONESIA - Ratna Artha Windari; Aldo Rico Geraldi (Arena Hukum, 2017)
Â AbstractThis research aims to analyze the sovereignty of the state related to the succession or separation of East Timor from the territory of the Republic of Indonesia. In addition, this research also analyzes the implementation of the pacta tertiis nec nocent nec prosunt principle related to the Timor Gap Treaty between Indonesia and Australia. This research is used normative law research by collecting secondary data. Data is collected using methods of literary study by collecting legal material and information in the form of legal materials of primary, secondary, and tertiary. In order to get a clear explanation, the data will be arranged systematically and analyzed using descriptive methods. The results of this research show that Timor Leste has the sovereignty and legal capacity to provide protection to its citizens, territories and activities. But the power of the state is limited to the territory, the emergence of the power of another country, and lies in international law. In relation to the succession of the state, since the United Nations Transition Administration in East Timor on behalf of the United Nations handed over the sovereignty of East Timor on 26 May 2002 to the people of Timor Leste, it indicates the succession of the state. Whereas in relation to the pacta tertiis nec nocent nec prosunt principle, Article 34 of the Vienna Convention 1969 on the International Treaty firmly adheres to the the pacta tertiis nec nocent nec prosunt principle which means that the treaty can not grant rights and obligations to third parties. Under the pratice of the nec noc prosunt nactant pacta, the continental shelf area to the south of East Timor which is the object of the Timor Gap Treaty is no longer under Indonesian sovereignty, but is under East Timorese sovereignty as a consequence of East Timor's independence.Â Abstrak Penelitian ini bertujuan untuk menganalisis paham kedaulatan negara terkait dengan suksesi atau pemisahan Timor Timur dari wilayah Republik Indonesia. Selain itu, penelitian ini juga menganalisis asas pacta tertiis nec nocent nec prosunt terkait dengan Perjanjian Celah Timor antara Indonesia dan Australia. Penelitian ini menggunakan penelitian hukum normatif dengan mengumpulkan data sekunder. Pengumpulan data dilakukan menggunakan metode studi kepustakaan Hasil penelitian menunjukkan bahwa Timor Leste memiliki kedaulatan dan kemampuan hukum untuk memberikan perlindungan pada warga negaranya, wilayah, dan kegiatannya. Namun kekuasaan negara terbatas pada wilayah, munculnya kekuasaan suatu negara lain, serta terletak pada hukum internasional. Terkait dengan suksesi negara, sejak United Nations Transition Administration in east Timor atas nama PBB menyerahkan kedaulatan Timor Leste pada tanggal 26 Mei 2002 kepada bangsa Timor Leste, hal tersebut menandakan terjadinya suksesi negara. Sedangkan terkait dengan asas pacta tertiis nec nocent nec prosunt, Pasal 34 Konvensi Wina 1969 tentang Perjanjian Internasional dengan tegas menganut asas pacta tertiis nec nocent nec prosunt yang berarti bahwa perjanjian tidak dapat memberikan hak dan kewajiban pada pihak ketiga. Dengan asas pacta tertiis nec nocent nec prosunt, maka wilayah landas kontinen yang berada di sebelah selatan Timor Timur yang merupakan obyek dari Perjanjian Celah Timor tidak lagi berada di bawah kedaulatan Indonesia, tetapi berada di bawah kedaulatan Timor Leste sebagai konsekuensi atas kemerdekaan Timor Timur.